Analisis Perbedaan Kinerja Keuangan Atas Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Terhadap Perusahaan di Subsektor Lembaga Keuangan - Fitra Oliyan (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
The development of a company can be seen from its financial performance so that it helps investors to help make investment decisions. The year 2020 has passed with the COVID-19 pandemic. However, this pandemic period will continue in 2021 so that the government at the beginning of the year imposed the Enforcement of Community Activity Restrictions (PPKM). So that anxiety about the limitations of carrying out activities is still felt. The activity of working from home or known as Work from Home becomes an obstacle because it will cause a domino effect on other business fields, especially in the financial sector which is listed on the Indonesia Stock Exchange in 2021. In this research, researchers are interested in the financial sector. Companies in the financial sector have a direct impact on this policy. The purpose of this research is to see whether companies in this sector are affected by the PPKM policy. This research uses a descriptive quantitative approach. This study will find differences in financial performance during the COVID-19 pandemic in the second year. More profit is generated in this sector, so it can be concluded that during the pandemic in 2021, many people do financing.